Социокультурные изменения в контексте глобальных процессов глазами населения Украины - Паращевин, М. (Социология: теория, методы, маркетинг, 2005)
The author of this article has made an attempt to determine how adult population of Ukraine perceives the consequences of some global processes both for the whole country and for citizens individually. The analysis was made on the basis of data from the All Ukrainian public opinion poll conducted in 2002 by Company on demand of the Pew Center Research organization. There was considered how the population of Ukraine accepted the increase in interrelations between our country and the others, how strong was the feeling of loss of their traditional mode of life and need for protection of this mode of life, what was the attitude to potential americanization of our culture as well as moral and ethical characteristics of the future generations of our population.